An Understanding the Pauline Christology Significance of Firstborn (Prototokos) In The Light of Paschal Theology: Critical Evaluation on Colossian 1: 15-20 - Wiryadinata, Halim (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2018)
Paul was claimed as the most controversial person in his theology. Many scholars said that he was influenced by Hellenistic Judaism in his theology; while others claimed it was affected by Jewish thinking. The concept of prototokos (firstborn) was stated being influenced by Hellenistic Judaism and did not imply the rest of New Testament Theology. Some said that firstborn in Colossian 1: 1520 was a hymn in praise of Christ, while others would say that firstborn in the Hymn Christology is congenial, but not identical with Pauls theology. This research aimed to show the concept of firstborn as the main window showed Pauline Christology significance in the light of Paschal theology. The methods used in this research were descriptive and biblical text analysis. The conclusion of this research is that the death of Christ is the main point to see how firstborn of all creation not counted as ontological in meaning, but it has the power to show the readers about Pauline Christology. The firstborn of all creation is seen in the context of redemptive history and bring the audience to see how powerful the title to see Pauline Christology.